2005
DOI: 10.1163/22941932-90000120
|View full text |Cite
|
Sign up to set email alerts
|

Radial Variations of Anatomical Characteristics and Specific gravity in Eucalyptus Camaldulensis Clones

Abstract: Five superior clones of Eucalyptus camaldulensis from in vitro propagation or tissue culture at the Sra Keaw plantation site in the eastern part of Thailand were selected for examining radial variations of anatomical characteristics and specific gravity. The age of the clones was 5 years at harvest. A 9-year-old tree grown from seed in the same site was also investigated. Results were as follows: 1) Mean specific gravity showed significantly different values among the 5 clones and the seedling. 2) Vessel densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
8

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 2 publications
4
14
0
8
Order By: Relevance
“…However, an observation on increasing fibre width in wood of seed-originated 45-year-old downy birch to more than 28 μm also exists (Bhat 1980). The difference observed here, regarding fibre width of seed-and sprout-originated downy birches, is also consistent with observations of some eucalypts (Veenin et al 2005). The fibres were slightly wider in relation to the length in sprout-originated than in seed-originated trunks, the length increasing more than the width.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, an observation on increasing fibre width in wood of seed-originated 45-year-old downy birch to more than 28 μm also exists (Bhat 1980). The difference observed here, regarding fibre width of seed-and sprout-originated downy birches, is also consistent with observations of some eucalypts (Veenin et al 2005). The fibres were slightly wider in relation to the length in sprout-originated than in seed-originated trunks, the length increasing more than the width.…”
Section: Discussionsupporting
confidence: 91%
“…In sprout-originated birches the slowing down of fibre lengthening occurred coincidently with the fibre width reaching its maximum. The comparable phenomena have been associated with changes leading to wood maturation (Ridoutt and Sands 1993, Bonham and Barnett 2001, Veenin et al 2005. Thus, the commencement of wood maturation may vary depending not only on species but also on the origin of the stem.…”
Section: Discussionmentioning
confidence: 88%
“…6c) showed that vessel size depended on the position within the stem. A similar pattern was observed in Eucalyptus camaldulensis, wherein vessel size increased from the pith to the bark side [29]. In all provenances that we examined, vessel lumen area (%) and the diameter of vessels ranged from 8.4 to 10.0% and 115 to 129 lm in the juvenile, and from 13.8 to 17.1% and 146 to 155 lm in the mature wood, respectively (Table 2).…”
Section: Anatomical Characteristics Of Woodsupporting
confidence: 78%
“…Wood element's dimensions were also non-significantly varied in L-34 clone of P. deltoides form bottom to top and pith to outwards (Gautam 2010). It showed no age impact on the dimensions of wood elements and regulating mostly homogeneous wood properties within the ramet (Pande 2005;Pande & Singh 2009;Veenin et al 2005). The same result is also true in the present study.…”
Section: Resultssupporting
confidence: 87%